Pedagogical Skills, Self-Efficacy and Content Knowledge Need For Shorthand Instructional Delivery of Lecturers in Public Tertiary Institutions in Niger State, Nigeria - Mohammed, Abdulrazak; Ibitoye, Olayinka; Haruna, Hassan (Papanda Publishier, 2024)
This study assessed the pedagogical skills, self-efficacy and content knowledge need for shorthand instructional delivery of lecturers in public tertiary institutions in Niger State, Nigeria. Three specific objectives and three research questions guided the study. Similarly, three null hypotheses were formulated and tested at 0.05 level of significance. The study covered shorthand lecturers from sixty public tertiary institution offering shorthand in Northern Nigeria. The design for the study was descriptive survey and the population was 125 shorthand lecturers. The entire 125 shorthand lecturers were used for the study. The instrument for data collection was a 4-points structured questionnaire developed by the researcher titled “Pedagogical Skills, Self-Efficacy and Content Knowledge Need for shorthand instructional Delivery” (PSSECNSID). The instrument was validated by 4 experts. Pilot study was conducted using tertiary institutions in Osun state who were not part of the subjects. The data collected from pilot study was analyzed using Cronbach Alpha method for reliability test and reliability co-efficient of 0.70 was obtained. The instrument was administered to the target respondents using direct approach and the researcher was assisted by 18 research assistants. Mean and standard deviation were used to answer the research questions, while Analysis of Variance (ANOVA) was used to test the null hypotheses at 0.05 level of significance. The study concluded that shorthand lecturers need pedagogical skills, self-efficacy and content knowledge for effective shorthand instructional delivery in public tertiary institutions in Niger State, Nigeria. Based on the findings, the study recommended, among others, that government and professional organizations should organize workshops and seminars that will improve the pedagogical skills, self-efficacy and content knowledge of shorthand lecturers in Niger State, Nigeria. Implication of these findings, among others, is that pedagogical skills need of shorthand lecturers for effective instructional delivery may not improve if training and re-training programme are not organized in public tertiary institutions offering shorthand in Niger State, Nigeria.